One‐pot synthesis of carbon dots using two different acids and their respective unique photoluminescence property. (11th May 2016) - Loi, Elaine; Ng, Roy Wei Chao; Chang, Melissa May Fung; Fong, Jessica Fung Yee; Ng, Yann Huey; Ng, Sing Muk
Abstract: Carbon dots, a new class of nanomaterial with unique optical property and have great potential in various applications. This work demonstrated the possibility of tuning the emission wavelength of carbon dots by simply changing the acid type used during synthesis. In particular, sulfuric and phosphoric acids and a mixture of the two were used to carbonize the same starting precursor, sucrose. This resulted in the isolation of carbon dots with blue (440 nm) and green (515 nm) emission. Interestingly, the use of an acid mixture at various ratios did not shift the initial emission profile, but did obviously alter the fluorescence efficiency of the peaks. This clearly showed that acid type can be used as an alternative tool to produce carbon dots that have different emissions using the same starting precursor. Copyright © 2016 John Wiley & Sons, Ltd.